Field guide to the common mangroves, seagrasses and algae of the Philippines - Calumpong, Hilconida P. (Bookmark, 1997)
Covers 26 genera with 39 species. Includes a thorough treatment of the 7 genera and 13 species of seagrasses. The algal treatments are incomplete however, depicting for green algae 24 genera, 41 species of the 37 genera, 220 species recorded, and similarly for the brown algae 9 genera, 18 species of 24 genera, 137 species, and for the red algae 34 genera, 48 species of 128 genera, 491 species. Because of the scope of this book, it can not possibly reflect the great diversity of algal species in the Philippines, many of which are undescribed.